Emerging economies and multinational enterprises - Tihanyi, Laszlo (College teacher) (Emerald, 2015)
Volume 28 of the Advances in international management focuses on the opportunities and challenges for multinational enterprises that consider emerging economies as their destinations or their homes. Chapters in this volume examine the rise of home-grown multinational enterprises in emerging economies and the challenges they face when they enter developed markets. They also analyze the co-evolution of and the dynamic interaction between market institutions and business organizations in emerging economies. The volume provides a forum for thought-provoking ideas, empirical research, and discussions, and is ideal for researchers and doctoral students whose work touches emerging markets.
Keywords: International business enterprises -- Developing countries.; elektronické knihy; electronic books